Synergistic Effects of Pulsed Lavage and Antimicrobial Therapy Against Staphylococcus aureus Biofilms in an in-vitro Model - Poilvache, Hervé; Ruiz-Sorribas, Albert; Sakoulas, George; Rodriguez-Villalobos, Hector; Cornu, Olivier; Van Bambeke, Françoise (Frontiers in Medicine, 2020)
Background: Prosthetic joint infections (PJI) are difficult to treat complications of joint arthroplasty. Debridement with implant retention is a common treatment strategy and frequently involves the use of pulsed lavage (PL). However, PL effects on biofilms and antibiotic activity have been scarcely studied in-vitro. We report the effects of PL, vancomycin or flucloxacillin used independently or in combination against Staphylococcus aureus biofilms. Methods: Biofilms of 3 methicillin-susceptible (MSSA) and of 3 methicillin-resistant (MRSA) S. aureus were grown on Ti6Al4V coupons in TGN (TSB + 1%glucose + 2%NaCl). After 24h, PL was applied to half the samples (50mL saline from 5cm). Samples were either reincubated for 24h in TGN or TGN + flucloxacillin or vancomycin. Analyses included CFUs counts, biomass assays or fluorescence microscopy. Results: PL transiently reduced bacterial counts by 3-4 Log10 CFU/coupon, but bacterial regrowth to baseline levels was seen after 24h. At 20mg/L, flucloxacillin reduced both the CFU counts ( 3 Log10 CFU/coupon) and biomass (-70%) in one MSSA only, while vancomycin had no effects against MRSA. PL combined with a 24h reincubation with vancomycin or flucloxacillin at 20mg/L was synergistic (-5-6.5 Log10 CFU/coupon; 81-100% biomass reduction). Fluorescence microscopy confirmed that PL removed most of the biofilm and that subsequent antibiotic treatment partially killed bacteria. Conclusions: While PL only transiently reduces the bacterial load and antibiotics at clinically relevant concentrations show no or limited activity on biofilms, their combination is synergistic against MRSA and MSSA biofilms. These results highlight the need for thorough PL before antibiotic administration in PJI.